Parque Estadual Serra Dourada, Goiás : usos, conflitos e disputas territoriais - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
The Serra Dourada State Park, a World Heritage Site, was created by the State Government of Goiás through Decree n. 5,768, of June 5, 2003. It is noteworthy that since 1997 the municipal environment secretariat had already considered the creation of the park. Then came the need, for different reasons and interests, for a new territorial delimitation of the Serra Dourada State Park, which took place in 2019. The conflicts arose from the divergence of interests in the uses and appropriations of the Park. This research discusses how the new delimitation of the Serra Dourada State Park configured uses, conflicts and disputes, in order to show the different political perspectives in the conception of the Biome-Cerrado territory. In the first part, a diagnosis of the Park is made, its location, physiography and historical context are presented. In the second part, a political perspective of parks is presented; how they emerged and how they take shape. And in the third part, the map of conflicts of interests, uses and appropriations is presented. To avoid additional financial costs with expropriation of areas, the Government of the State of Goiás, considered the improvements (houses, pasture area, farming, confinement, farm) as areas that had neither environmental attributes nor conservation interest. They were then excluded from the total area of the Park.
Keywords: Parque Serra Dourada; Delimitação; Território; Serra Dourada Park; Delimitation; Territory; CIENCIAS HUMANAS::GEOGRAFIA